Driving Miss Daisy - Beresford, Bruce; Zanuck, Richard D.; Zanuck, Lili Fini.; Uhry, Alfred; Freeman, Morgan; Tandy, Jessica; Aykroyd, Dan.; LuPone, Patti; Rolle, Esther; James, Peter, 1947 March 7-; Zimmer, Hans.; Warner, Mark (Mark Roy); et al. (Burbank, CA : Warner Home Video, 1997)
A joyous comedy about a head-strong southern lady and her ever-patient chauffeur.
Originally released as a motion picture in 1989.
Based on the play by Alfred Uhry.
Rated PG.
Director of photography, Peter James ; music, Hans Zimmer ; editor, Mark Warner.
Morgan Freeman, Jessica Tandy, Dan Aykroyd, Patti Lupone, Esther Rolle.
DVD, region 1; Dolby surround stereo; digitally processed.
Keywords: Older women -- Georgia -- Atlanta -- Drama; Chauffeurs -- Georgia -- Atlanta -- Drama; African American men -- Georgia -- Atlanta -- Drama; Friendship -- Drama; Mothers and sons -- Drama; Race relations -- Drama; Southern States -- Drama; Academy Awards (Motion pictures); DVD; Video; Video recordings for the hearing impaired; Film adaptations; Fiction films; Drama; Comedy films; Feature films; Films for the hearing impaired